The Suitability Of Coastal Area Development Based On Minawisata Concept in Pacitan District - Syahrial Nur Amri; Taslim Arifin (Pusat Riset Kelautan, 2017)
Minawisata concept is the implementation and integration of efforts to optimize the utilization of marine and coastal resources with action to maintain the sustainability and value of sustainability. This study aimed to determine the suitability of the coastal land development in Pacitan District based on the potential of marine and coastal areas in accordance to the minawisata concept. Study area covered seven districts along the coastline of Pacitan District, East Java Province, namely Donorejo, Pringkuku, Pacitan, Kebonagung, Tulakan, Ngadirejo, and Sudimoro District. The methodology used in this study is a combination of Geographic Information Systems analysis, satellite imagery interpretation, and field data processing. This study is limited to the identification of the potential of marine and coastal area, the suitability of land use, and the suitability of coastal area development based on the minawisata concept. The results show that there are three dominant utilizations of marine and coastal areas in Pacitan District, including: Marine Aquaculture, Capture Fisheries, and Beach Tourism. Based on the analysis on suitability of the marine and coastal area, seven districts in Pacitan are suitable for fisheries and beach tourism, while only two districts were suitable for marine aquaculture with several conditions, namely Pacitan District and Ngadirejo District. The implementation of minawisata concept for coastal area suitability based on the analysis of seven identified districts is feasible for further development.